2021
DOI: 10.3892/or.2021.8253
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of CDCA3 inhibits prostate cancer progression via NF‑κB/cyclin D1 signaling inactivation and p21 accumulation

Abstract: Dysregulation of the cell cycle contributes to tumor progression. Cell division cycle-associated 3 (CDCA3) is a known trigger of mitotic entry and has been demonstrated to be constitutively upregulated in tumors. It is therefore associated with carcinogenic properties reported in various cancers. However, the role of CDCA3 in prostate cancer is unclear. In the present study, western blotting and analysis of gene expression profiling datasets determined that CDCA3 expression was upregulated in prostate cancer a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
(57 reference statements)
2
9
0
Order By: Relevance
“…47 Knockdown of CDCA3 inhibited prostate cancer progression by accumulating p21 and inhibiting cyclin D1 through inactivating the NF-κB signaling pathway. 48 Here, we further confirmed that CDCA3 inhibited p53 and p21 expression in TNBC cells, indicating the inactivation of CDCA3 on p53/p21 signaling. However, depletion of CDCA3 triggered an increase in p21 independent of p53 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…47 Knockdown of CDCA3 inhibited prostate cancer progression by accumulating p21 and inhibiting cyclin D1 through inactivating the NF-κB signaling pathway. 48 Here, we further confirmed that CDCA3 inhibited p53 and p21 expression in TNBC cells, indicating the inactivation of CDCA3 on p53/p21 signaling. However, depletion of CDCA3 triggered an increase in p21 independent of p53 in NSCLC cells.…”
Section: Discussionsupporting
confidence: 78%
“…CDCA3 was also demonstrated to promote cell proliferation and tumorigenesis in colorectal cancer by repressing p21 expression 47 . Knockdown of CDCA3 inhibited prostate cancer progression by accumulating p21 and inhibiting cyclin D1 through inactivating the NF‐κB signaling pathway 48 . Here, we further confirmed that CDCA3 inhibited p53 and p21 expression in TNBC cells, indicating the inactivation of CDCA3 on p53/p21 signaling.…”
Section: Discussionsupporting
confidence: 72%
“…More and more studies have confirmed that dysregulated expression of CDCA3 plays a vital role in cancer progression. The clinical treatment effect of cancer patients with high expression of CDCA3 is worse, and CDCA3 may become a new potential prognostic marker and a new therapeutic target for cancer [42][43][44][45].…”
Section: Discussionmentioning
confidence: 99%
“…However, controversial outcomes still exist; for example, knockdown of CDCA3 in NCSLC reduces the proliferation of NCSLC cells by stagnating them in G2/ M phase (23). In colorectal cancer (CRC) and PC, CDCA3 induces cell cycle arrest in the G1 phase (24,25). In addition, CDCA3 also affects the progression of GC through epigenetics.…”
Section: Discussionmentioning
confidence: 99%
“…KEGG pathway analysis indicated that CDCA3 was involved in cell cycle, proteasome, spliceosome, and DNA replication pathways. Studies have shown that CDCA3 activates the nuclear factor kappa B (NF-KB)/cyclin D1 signaling pathway and promotes cancer cell proliferation in CRC and PC (25). In breast cancer and pancreatic cancer, CDCA3 plays a critical role in tumor progression through activation of the phosphoinositide 3-kinases (PI3K)/AKT pathway (7,32).…”
Section: Discussionmentioning
confidence: 99%